Structures and mechanical properties of talc and carbon black reinforced high density polyethylene composites : Effects of organic and inorganic fillers (Journal of Bangladesh Academy of Sciences, 2013)
Organic filler like carbon black (CB) and inorganic filler like talc (T) with 0, 0.5, 1.0, 10, 20 and 40 wt% were separately loaded in high density polyethylene (HDPE) by the extrusion moulding method at 160oC. Then, different sets of filler loaded HDPE composites were prepared using the compression moulding technique, and their structures and mechanical properties were characterized. The pure HDPE sample, as examined by the X-ray diffraction (XRD) technique, showed orthorhombic structure, which did not change either with filler types or with their concentration. The only variations found in the structure are the changes of crystallinity and crystallized size that depend on both types of fillers and their concentrations. Incorporation of CB in HDPE emphasizes the crystallinity and crystallized size more than that of T. The tensile strength of the composite decreases with the increase of both types of fillers, and this decrease is explained on the basis of Nielson model, which basically describes a poor interaction between filler and HDPE matrix. An increase of Youngs modulus of 350% is observed with the increasing CB and T contents, representing an increase of the stiffness in the materials. Flexural strength increased with the increase of CB content but decreased with the increase of talc content. Although the microhardness was observed to increase with both types of fillers, the hardness value was 80% higher for CB loaded-composites than that of T at 40 wt% filler content. These findings strongly indicate that the compatibility of HDPE is better with organic filler than with inorganic one. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15675 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 11-20, 2013